Studying Pressure Variation in a Fractured Carbonate Reservoir Producing Under Steam Flooding EOR with Multiple Fracture Matrix Arrangements (Rudarsko-geološko-naftni zbornik, 2025)
The viscous oil reserves present around the world are estimated to be 2 trillion barrels, but to date, the lack of suitable technology for production causes these reserves present in complex reservoirs to negligibly contribute to world daily production. Most of these fractured reservoirs possess enormous heterogeneity due to high contrast between petrophysical parameters like porosity and permeability. Evaluating both the matrix and fractures is crucial for understanding these complex types of reservoirs. In oil and gas reservoirs, pressure is vital for maintaining the flow of hydrocarbons. Reservoir pressure helps push oil and gas through porous rock formations to production wells. The same pressure variation becomes very important during steam injection for recovering heavy oil from fractured carbonate reservoir. This study aims to capture pressure variation in different matrix-fracture arrangements. COMSOL Multiphysics® is used in this study, to map the pressure variation in a fractured carbonate reservoir producing under the steam flooding Enhanced Oil Recovery (EOR) technique. The results presented in this study reveal distinct pressure profiles for various fracture arrangements, including single horizontal & vertical fractures, closed loop arrangements, open loop arrangements, and irregular fracture networks. In a closed loop arrangement of matrix & fracture, pressure variations and compartmentalization effects are observed, necessitating precise management strategies to address isolated pressure responses. However, in an open loop arrangement, there are early pressure disturbances with dense fractures and delayed responses with wider fracture spacing, highlighting the influence of fracture density and spacing on fluid flow efficiency. This research contributes valuable insight for improved reservoir management.